Nonlinear association of the systemic immune-inflammatory index with mortality in diabetic patients - Meng, Chunli; Liu, Kai (Frontiers in Endocrinology, 2024)
It has been demonstrated that in diabetic patients, an elevated neutrophil-lymphocyte ratio (NLR) is independently connected with higher cardiovascular and all-cause mortality. It is unclear, however, if the systemic immune-inflammatory index (SII) and the mortality rate among diabetic patients are related. Investigating the linkage between SII and diabetes patients' risk of cardiovascular and all-cause death was the aim of the study.4972 diabetics who were chosen from six rounds of the National Health and Nutrition Examination Survey (NHANES) between 2005 and 2016 were the study's participants. The optimal SII threshold with the highest correlation with survival outcomes was identified by applying the Maximum Selection Ranking Statistical Method (MSRSM). To assess the relationship between SII and cardiovascular and all-cause mortality in diabetics, subgroup analysis and Cox regression modeling were employed. Furthermore, smoothed curve fitting was utilized to determine the nonlinear relationship of them.Over the course of a median follow-up of 69 months (interquartile range [IQR], 54-123 months), 1,172 (23.6%) of the 4,972 diabetic patients passed away. These deaths included 332 (6.7%) cardiovascular deaths and 840 (16.9%) non-cardiovascular deaths. Individuals were categorized into higher (>983.5714) and lower ( ≤ 983.5714) SII groups according to MSRSM. In multi-variable adjusted models, subjects with higher SII had a significantly increased chance of dying from cardiovascular disease (HR 2.05; 95% confidence interval (CI):1.42,2.97) and from all causes (HR 1.60; 95% CI:1.22,1.99). Kplan-Meier curves showed similar results. Subgroup studies based on age, sex, BMI, drinking, smoking, and hypertension revealed that the connection maintained intact. The previously stated variables and SII did not significantly interact (p interaction > 0.05). In diabetic patients, smooth curve fitting revealed a nonlinear correlation between SII and mortality.In diabetic patients, elevated SII is linked to higher cardiovascular and all-cause mortality.